Hedonic Consumption: Emerging Concepts, Methods and Propositions - Hirschman, Elizabeth C.; Holbrook, Morris B. (Journal of Marketing, 1982)
This paper defines hedonic consumption as those facets of consumer behavior that relate to the multisensory, fantasy and emotive aspects of product usage experience. After delineating these concepts, their theoretical antecedents are traced, followed by a discussion of differences between the traditional and hedonic views, methodological implications of the latter approach, and behavioral propositions in four substantive areas relevant to hedonic consumption—mental constructs, product classes, product usage and individual differences. Conclusions concern the usefulness of the hedonic perspective in supplementing and extending marketing research on consumer behavior.